Extract from the stem of Tinospora crispa (L.) Hook. f. & Thomson extends life span and decreases stress-induced mortality in Drosophila melanogaster - Nattapong Wongchum; Ananya Dechakhamphu (Faculty of Pharmacy, Mahidol University, 2022)
Aging plays a significant role in the development of degenerative diseases. The stem of Tinospora crispa has been recorded to use as longevity medicine in ancient Thai manuscripts. However, there is no experimental data to verify this property. This study aimed to verify the anti-aging activity of T. crispa extract (TCE) in Drosophila melanogaster. The effects of TCE on the life span and the resistance to stressors, including free radicals, heat and cold shocks, and starvation, were investigated in D. melanogaster. When compared to the control diet, TCE supplementation at 20 mg/mL in mixed diets increased in the 50% survival time by 18.37%. On days 25 and 40, TCE-treated flies showed a significant increase in climbing ability when compared to control flies. In TCE-treated flies, significant increases in superoxide dismutase (SOD1 and SOD2) and catalase (CAT) activities were found at days 25 and 40. The findings of the paraquat and H2O2 challenge tests revealed that flies given TCE at 20 mg/mL survived longer than control flies. TCE supplementation increased resistance to starvation and acetic acid-induced stress, as well as recovery from cold and heat shocks. This study provides experimental data on the significance of dietary TCE supplementation in extending life span and reducing stress-induced mortality in Drosophila.